2015
DOI: 10.4103/1319-2442.160211
|View full text |Cite
|
Sign up to set email alerts
|

Liddle′s syndrome: A case report

Abstract: Liddle's syndrome or pseudoaldosteronism is a rare autosomal dominant disease mimicking primary hyperaldosteronism, characterized by early-onset hypertension, hypokalemia and hypoaldosteronism, caused by excessive salt and water reabsorption in the distal nephron. As of 2008, there are <30 pedigrees or isolated cases that have been reported worldwide. We present an isolated case of a Liddle's syndrome in a 48-year-old female. A 48-year-old female presented to the clinic with palpitation and a three to four-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Teoh et al reported three cases of Liddle from Department of Pediatrics, University of Louisville, Kentucky USA with almost similar age group and clinical pictures as our case 8. Patel and Kuriacose reported a case of Liddle syndrome from Johnson City, Tennessee USA, but the age of the patient was 48 years 2. Tetti et al reported a case of Liddle in a 13-year-old Caucasian boy with history of sudden death of a sibling, just like in our case 11.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Teoh et al reported three cases of Liddle from Department of Pediatrics, University of Louisville, Kentucky USA with almost similar age group and clinical pictures as our case 8. Patel and Kuriacose reported a case of Liddle syndrome from Johnson City, Tennessee USA, but the age of the patient was 48 years 2. Tetti et al reported a case of Liddle in a 13-year-old Caucasian boy with history of sudden death of a sibling, just like in our case 11.…”
supporting
confidence: 64%
“…1 This rare syndrome has an autosomal dominant inheritance and typically comprises of hypertension, hypokalemia and metabolic alkalosis. 2 Although the affected individuals have high blood pressure since childhood, early diagnosis is missed in some cases. 3 Hypokalemia, associated with this disorder causes muscle weakness, fatigue, pain and palpitations.…”
Section: Introductionmentioning
confidence: 99%
“…14 Sementara itu, Liddle syndrome merupakan kelainan autosomal dominan yang ditandai dengan hipertensi, hipokalemia, alkalosis metabolik, namun pada sindrom ini didapatkan kadar aldosteron yang normal atau rendah. 15 Conn's syndrome ditandai dengan peningkatan kadar aldosteron, kadar renin yang rendah, hipertensi, hipokalemia, dan alkalosis metabolik. 3,[5][6][7] Untuk menegakkan diagnosis selanjutnya, maka pada pasien ini dilakukan pemeriksaan MRI abdomen dan didapatkan tumor adrenal kiri dengan ukuran 1,7 x 1,5 cm, serta dilakukan pemeriksaan kadar aldosteron dan didapatkan nilai <0,97 ng/dl.…”
Section: Diskusiunclassified
“…In contrast, rare-earth complexes of cyclobutadienyl (Cb) ligands, [h 4 -C 4 R 4 ] 2À ,a re conspicuousb yt heir absence, and only one actinide cyclobutadienylc omplex is known. [9] The paucity of fblock cyclobutadienyl compounds is presumably due to the rarity of cyclobutadiene pro-ligands,a nd the fact that rareearth elements have not yet been shown to mediate cyclobutadiene formation via alkyne cyclo-dimerization. [10] With the aim of isolating the first rare-earth cyclobutadienyl complexes,w er easoned that as alt metathesis reaction betweena na lkali metals alt of 1,2,3,4-tetrakis(trimethylsilyl)cyclobuta-1,3-diene [11] and ar are-earth halide could furnish ac ompoundc ontaining the "squarocene" complex[ M{h 4 -C 4 (SiMe 3 ) 4 } 2 ] À .T hus,t he reaction of 1,2,3,4-tetrakis(trimethylsilyl)cyclobuta-1,3-diene with potassium metal in THF produced[ K 2 {h 4 -C 4 (SiMe 3 ) 4 }] (1)a sayellow powder in 72 %y ield.…”
mentioning
confidence: 99%